Pakistan at 100 : Human Capital - Ahmed, Syud Amer; Cho, Yoonyoung; Fasih, Tazeen (World Bank, Washington, DC, 2019)
This policy note was prepared in parallel to the report Pakistan at 100, Shaping the Future. The report Pakistan at 100 discusses options to accelerate and sustain growth in Pakistan so that the country becomes an upper middle-income country when it turns 100 years old in 2047. This policy note discusses Pakistan’s greatest asset- its large population, requiring more and better investment to become a demographic dividend that supports growth for decades to come.